Effectiveness of Inquiry Learning Models to Improve Students' Critical Thinking Ability - Samadun Samadun; Rahyu Setiani; Dwikoranto Dwikoranto; Marsini Marsini (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2023)
Objective: This study aims to determine the effectiveness of the inquiry learning model in improving students' critical thinking skills. This type of research is a literature study using articles related to the influence of the inquiry learning model on students' critical thinking skills. Method: The method used is the descriptive qualitative research method. The data source used in this study is secondary data, namely articles that have been published. These articles were sourced from Google Scholar, Open Access Journal, sinta indexed journals, and national university websites between 2012 and 2022. Eight journals were suitable for research on critical thinking skills and inquiry. Results: The result of this study is that it is known that the inquiry learning model has a significant influence on improving students' critical thinking skills. There is a significant difference in critical thinking skills between students who use the inquiry learning model and those who are taught with the non-inquiry learning model. Novelty: The guided inquiry learning model has proven to be effectively applied to improve students' critical thinking skills.